Problems of development policies - Thanos, Kōnstantinos A. (Athens, Bank of Greece, 1969)
The prevailing confusion with regard to the content and aims of economic planning has in many cases had unfavourable repercaussions on monetary policy and banking organization in general.Many countries in Latin America and the Caribbean have achieved considerable economic growth, yet the region still faces many seemingly intractable problems. The conventional wisdom in development agencies - that prioritization is impossible and that everything must be done - is simply not effective. Latin American Development Priorities shows how limited resources could be used for the greatest benefit of the Latin .
aia 13/02/2019
Loans
Keywords: Economic development; Greece